Metode Tafsri Modern: Al-Manār, Al-Marāghi, dan Al-Misbāḥ - Nana Mahrani (Hikmah, 2015)
Modern methods of interpretation that the interpretation of Al-Manār, Al-Marāghi and Al-Misbāḫ basically want to enable the main objective of the presence of the Qu’an, that is, as a guidance and giving a way out for the various problems of mankind. Therefore, modern interpretation colored by efforts to unearth the Koran in the midst of life of Muslims. The commentators wanted to prove that the Qur'an really is universal that can address the problems of the people.